2015
DOI: 10.1097/fjc.0000000000000313
|View full text |Cite
|
Sign up to set email alerts
|

Oxidant and Inflammatory Mechanisms and Targeted Therapy in Atrial Fibrillation

Abstract: Atrial fibrillation (AF) is an important cause of stroke and risk factor for heart failure and death. Current pharmacologic treatments for AF have limited efficacy, and treatments that more directly target the underlying causes of AF are needed. Oxidant stress and inflammatory activation are inter-related pathways that promote atrial electrical and structural remodeling, leading to atrial ectopy, interstitial fibrosis and increased stroke risk. This review evaluates the impact of common stressors on atrial oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
53
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 70 publications
(82 reference statements)
0
53
0
2
Order By: Relevance
“…Unfortunately, the extent of a systemic inflammatory response following catheter ablation was unclear. Many clinical trials, meta‐analyses, and guidelines admitted that oxidative stress and inflammatory activation had interrelated pathways that promoted electrical and structural atrial remodeling . Therefore, it may be strongly implicated at the AF onset.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Unfortunately, the extent of a systemic inflammatory response following catheter ablation was unclear. Many clinical trials, meta‐analyses, and guidelines admitted that oxidative stress and inflammatory activation had interrelated pathways that promoted electrical and structural atrial remodeling . Therefore, it may be strongly implicated at the AF onset.…”
Section: Discussionmentioning
confidence: 95%
“…Many clinical trials, meta-analyses, and guidelines admitted that oxidative stress and inflammatory activation had interrelated pathways that promoted electrical and structural atrial remodeling. 22 Therefore, it may be strongly implicated at the AF onset. Statins, which impact oxidative and inflammatory mechanisms, protect against electrical remodeling associated with atrial tachycardia pacing.…”
Section: Discussionmentioning
confidence: 99%
“…The underlying mechanism for the correlation between particular matter and AF has yet been clearly demonstrated. A great number of studies suggested that particular matter cause oxidative stress, cardiovascular inflammation, endothelial dysfunction, high C‐reactive protein level, cardiac ischemia, and right atrial pressure, which were all related to atrial remodeling and AF pathophysiology . In addition, acute autonomic imbalance associated with exposure to particular matter may also induce AF …”
Section: Discussionmentioning
confidence: 99%
“…A great number of studies suggested that particular matter cause oxidative stress, cardiovascular inflammation, endothelial dysfunction, high C-reactive protein level, cardiac ischemia, and right atrial pressure, 10,[23][24][25][26] which were all related to atrial remodeling and AF pathophysiology. [27][28][29][30] In addition, acute autonomic imbalance associated with exposure to particular matter may also induce AF. 31 Contrary to previous studies, we did not find significant asso- increasing hospitalizations and premature mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Morphological and functional comparisons of atrial tissue from patients with or without diabetes have revealed that fibrosis was more elevated in diabetic atria [17]. Furthermore, atria from patients with T2DM and AF consistently display evidence for increased oxidative stress, suggesting that the oxidative stress and/ or underlying mechanisms may represent a T2DM-specific therapeutic target for AF [18,19].…”
Section: Introductionmentioning
confidence: 99%